Vaccination opportunity in children up to 6 months old born in 2017 and 2018 in the city of Londrina-PR, Brazil: a population-based survey - Heloísa Dias Brites; Ana Paula França; José Cássio de Moraes; Adriana Ilha da Silva; Alberto Novaes Ramos Jr.; Ana Paula França; Andrea de Nazaré Marvão Oliveira; Antonio Fernando Boing; Carla Magda Allan Santos Domingues; Consuelo Silva de Oliveira; Ethel Leonor Noia Maciel; Ione Aquemi Guibu; et al. (Epidemiologia e Serviços de Saúde)
ABSTRACT Objective To evaluate opportunity for vaccination in children born alive in Londrina, up to 6 months old and the relationship between socioeconomic stratum and vaccination regularity. Method Population survey study based on a retrospective cohort of children born in 2017 and 2018 that identified vaccines not administered in a given session. Vaccination regularity was compared between socioeconomic strata using Pearson’s chi-square test. Results Out of 456 vaccination cards, the proportion of vaccination opportunities not recovered for doses to be administered at birth and at two, four and six months was 5.0% (95%CI 3.1;7.5), 4. 5% (95%CI 2.8;6.9), 7.2% (95%CI 5.0;10.2) and 2.1% (95%CI 1.0;4.0), respectively. There was no statistical difference in vaccination regularity between the strata. Conclusion Missed opportunities for vaccination were found at all ages. Socioeconomic stratum did not influence vaccination regularity.